The role of social support and proactive supervisor behavior in the proactive behavior of employees - Miselytė, Marija; Bagdžiūnienė, Dalia (Psichologija, 2018)
The proactive behavior of employees is becoming more and more important in contemporary organizations, but less attention is paid to the impact that the proactive behavior of supervisors has on promoting proactivity in the behavior of employees. Meanwhile, there is a growing amount of research on the role of social support in encouraging proactive behavior, but research data are contradictory and there is no clear understanding of the role of different forms of social support (organizational, coworker and supervisor) on employee proactive behavior and its types (work, person-environment fit and strategic). The study aims to analyze the relations between supervisor proactive behavior, support on the levels of organizational, coworker and supervisor and employee proactive behavior as well as its types (work, person-environment fit and strategic). The study method consists an online survey and a sample of 206 employees (79 males and 127 females, aged 19 to 64 years) working in various Lithuanian organizations, who had participated in online survey. The results have shown that organizational, coworker and supervisor support are positively related with the proactive behavior of employees, but only organizational support is a predictor for two types of proactive behavior – strategic and work. Meanwhile, there is no direct effect between the proactive behavior of supervisors and employees. This connection occurs only if employees receive support on the organizational level as well as from their coworkers and supervisors; however, this relation is not the same for all types of proactive behavior. Support on the organizational level and from coworkers reinforces the relation between supervisor proactive behavior and employee proactive strategic behavior; supervisor support reinforces the relation between supervisor proactive behavior and employee proactive person-environment fit behavior.